Study Regarding the Policy of Non-Educating School Principals (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research aims to find out the reasons for the emergence of the non-educating school principal policy and find solutions for the appointment of non-educating school principals, as well as finding out the results of the non-educating school principal policy. This research is qualitative research, data collection uses interviews and documentation. The results of this research show that the policies of non-educating school principals have been regulated in legislation, one of which is Permendikbun No. 40 of 2021. Then the solution for non-educating school principals is a Letter from the Director General of Teachers and Education Personnel Number 8963/B.B1.1/ PR/2019 Regarding the PPG Program for School Principals Who Do Not Have an Educator Certificate. This policy can provide opportunities for non-educating school principals to obtain an educator certificate.